2014
DOI: 10.1002/bin.1379
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Video Modeling Combined With Self‐monitoring to Increase Rates of On‐task Behavior

Abstract: The study investigated the effectiveness of an intervention package consisting of self‐monitoring and video modeling to increase on‐task behavior during independent seatwork time in math. Four students in either the second or third grade, identified as displaying high rates of off‐task behavior by their classroom teacher, were included in the study. Results showed immediate, large, and durable changes in on‐task behavior for each of the four participants. At baseline, on‐task behavior of the participants while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Results of both studies indicated immediate improvements in the level of on-task behavior. Additionally, findings of King et al (2014) suggest that effects may be maintained following the termination of intervention procedures. In a case study evaluating the effects of a combined intervention on off-task behavior of a student with attention deficit-hyperactivity disorder, Blood, Johnson, Ridenour, Simmons, and Crouch (2011) found a combined intervention to be more effective than video modeling alone for increasing on-task behavior.…”
Section: Combined Intervention Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of both studies indicated immediate improvements in the level of on-task behavior. Additionally, findings of King et al (2014) suggest that effects may be maintained following the termination of intervention procedures. In a case study evaluating the effects of a combined intervention on off-task behavior of a student with attention deficit-hyperactivity disorder, Blood, Johnson, Ridenour, Simmons, and Crouch (2011) found a combined intervention to be more effective than video modeling alone for increasing on-task behavior.…”
Section: Combined Intervention Approachesmentioning
confidence: 99%
“…In a case study evaluating the effects of a combined intervention on off-task behavior of a student with attention deficit-hyperactivity disorder, Blood, Johnson, Ridenour, Simmons, and Crouch (2011) found a combined intervention to be more effective than video modeling alone for increasing on-task behavior. Although combined intervention strategies may require additional planning for implementation, they may be capable of overcoming decreasing maintenance effects that are associated with discontinuation of self-monitoring interventions (Amato-Zech et al, 2006;King et al, 2014;Kraemer et al, 2012), while producing improvements in on-task behavior greater than might be expected with video modeling alone (i.e., Blood et al, 2011).…”
Section: Combined Intervention Approachesmentioning
confidence: 99%
“…The authors present basic empirical evidence that supports the independent methodological components utilized in On-Task in a Box (i.e., self-monitoring, self-graphing, electronic prompting, peer modeling, self-modeling, and Fast-Hands Animation) as well as two studies that implemented the program design as a whole (i.e., Clare et al 2000;King 2012). The presentation of empirical data in this section is useful to facilitators who may not have either the time or experience to research and interpret empirical data.…”
Section: Does It Work?mentioning
confidence: 92%
“…Its focus is on kids in grades 1-6 who are off-task more than 50 % of the time. Studies that used similar procedures as On-Task in a Box have been shown to improve student's rates of on-task behaviors by an average of 33-38 % in grades 2-5, and these studies are noted (Clare 1992;King 2012). The authors suggest that those administering the program be school employees with a background in behavioral management principles and applications; however, a review of On-Task in a Box suggests that the program could have utility in other settings as well (e.g., home or hospital).…”
Section: Program Overviewmentioning
confidence: 98%
“…On-task behavior was measured every 10 seconds using whole interval recording (Carnett et al, 2014;Gourwitz, 2014;King, Radley, Jenson, Clark, & O'Neill, 2014) during a 15-minute interactive class period. The mobile application, Intervals, an ABA interval recording application (Mays, 2013), was used to signal a 10 second interval as data collectors used pencils to record the occurrence and nonoccurrence of on-task behavior of students on data sheets (Appendix B).…”
Section: Student Datamentioning
confidence: 99%